Peran System Umpan Balik pada Pengembangan dan Pengelolaan Manajemen Terpadu terhadap Mutu Pelayanan Pendidikan Vokasi Maritim - sari, Dian kurnianing; Widiatmaja, Arya; khamdilah, Ali (CV. Kalimasada Group, 2025)
Monitoring, evaluation and actions taken by the management team towards quality education according to national and international standards and convincing prospective students as regular customers of educational institutions and stakeholders as users of graduate services. Against the background of changes in the perspective of students in determining educational choices in market share competition, it becomes a threat to the sustainability of educational institutions and the main problem is maintaining the quality of education management quality in maintaining the level of student satisfaction. The purpose of this research is intended to determine the role of feedback on the management and development of maritime vocational education, which is intended to describe the input system, process, output and feedback from management management in order to get a breakthrough or a good formula about ease of control. The method used in this research is descriptive qualitative is a combination of two methods, namely descriptive and qualitative. This research will later display the results of the data as it is or without the manipulation process. The results of the data analysis obtained can describe quickly, precisely and minimize the occurrence of a new policy from the management of educational institutions in overcoming the unfavorable views of prospective students as customers for educational institutions.